2014
DOI: 10.1093/eurheartj/ehu039
|View full text |Cite
|
Sign up to set email alerts
|

The association between older age and receipt of care and outcomes in patients with acute coronary syndromes: a cohort study of the Myocardial Ischaemia National Audit Project (MINAP)

Abstract: We found an incremental reduction in the use of evidence-based therapies with increasing age using a national ACS registry cohort. While survival benefit from more intensive management reduced with older age, better survival was associated with intensive management at all ages highlighting the requirement to improve standard of care in older patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 26 publications
7
78
1
Order By: Relevance
“…One other limitation was that we did not have information on reperfusion therapy for patients. However, previously analyses within MINAP have reported that receipt of evidence-based cardiac medications post-ACS is less in older age groups,26 and we expect that our cohort will be similar to other cohorts in literature where it has been reported that younger patients are more likely to receive reperfusion therapy 27. Another limitation was that we do not have information on time to therapy as we expect that delay in presentation may be associated with delayed treatment and worse outcomes.…”
Section: Study Limitationssupporting
confidence: 62%
“…One other limitation was that we did not have information on reperfusion therapy for patients. However, previously analyses within MINAP have reported that receipt of evidence-based cardiac medications post-ACS is less in older age groups,26 and we expect that our cohort will be similar to other cohorts in literature where it has been reported that younger patients are more likely to receive reperfusion therapy 27. Another limitation was that we do not have information on time to therapy as we expect that delay in presentation may be associated with delayed treatment and worse outcomes.…”
Section: Study Limitationssupporting
confidence: 62%
“…Increased mortality risk in the presence of comorbidities likely relates to a myriad of pathological processes (such as dyslipidemia, chronic inflammation, endothelial dysfunction, hypertension, volume overload, impaired left ventricular function, microvascular disease, and immune compromise). [19][20][21][22] Whereas age-adjusted stroke incidence rates in high-income countries have decreased by 42% since the 1970s, the stroke incidence rates in low-to middle-income countries have more than doubled during this period (52 per 100 000 and 117 per 100 000 person-years, respectively; P<0.0001) with little sign of slowing. 23 As a result, the incidence of stroke in low-to middle-income countries has now exceeded that of highincome countries.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients presenting with acute coronary syndromes are at high risk even after successful coronary intervention 43. For patients over 75 years, the presence of comorbidities such as chronic kidney disease, significant LV dysfunction, CHF, chronic lung disease, anaemia and peripheral vascular disease increase the 1 year mortality risk substantially.…”
Section: Which Patients With Heart Disease Benefit From Fcp?mentioning
confidence: 99%